A piRNA utilizes HILI and HIWI2 mediated pathway to down-regulate ferritin heavy chain 1 mRNA in human somatic cells. Issue 20 (9th August 2018) - Balaratnam, Sumirtha; West, Nicole; Basu, Soumitra
Abstract: The piwi interacting RNAs (piRNAs) are small non-coding RNAs that specifically bind to the PIWI proteins, a functional requirement. The piRNAs regulate germline development, transposons control, and gene expression. However, piRNA-mediated post-transcriptional gene regulation in human somatic cells is not well understood. We discovered a human piRNA (piR-FTH1) which has a complementary sequence in the ferritin heavy chain 1 ( Fth1 ) mRNA. We demonstrated that expression of piR-FTH1 and Fth1 are inversely correlated in the tested tumor cell lines. We found that piR-FTH1 negatively regulates the Fth1 expression at post-transcriptional level in triple negative breast cancer (TNBC) cells. Additionally, we confirmed that transfected piR-FTH1 knocks down the Fth1 mRNA via the HIWI2 and HILI mediated mechanism. piR-FTH1 mediated Fth1 repression also increased doxorubicin sensitivity by a remarkable 20-fold in TNBC cells. Since the current piRNA-mediated knockdowns of target mRNA are mostly reported in germ line cells, piRNA-mediated post-transcriptional gene regulation in somatic cells is rather unique in its application and mechanistically uses an alternative pathway to siRNA and miRNA. This work begins to lay the groundwork with a broader impact on treatment of various diseases that are linked to elevated levels of specific mRNAs which have a piRNA target.